PELATIHAN PEMBUATAN KOMPOSTER DAN LUBANG BIOPORI SEBAGAI SOLUSI PERMASALAHAN SAMPAH ORGANIK DI LINGKUNGAN KRANGGOT KOTA CILEGON - Dhamar Lestari, Retno Sulistyo (Jurnal Pengabdian Dinamika, 2023)
Waste management, both organic and inorganic is one of the common problems in the commynity.Community development and transfer of technology on composting and biopores hole techniqueis an effort to enhance the potential of the surrounding environment in the form of residualorganic waste. This event was held in Kranggot village Cilegon District. The method used in thisresearch is the provision of material and Focus Group Discussion. Common problem is thehouseholds waste left unsorted and directly sent to the garbage collector have made the numberof solid waste piling up in the dumping site. This program focus in changing people’s mindset inhandling the household waste, sort the waste, and process the organic waste, installing bioporeson every house and open areas and making biocomposter to transform organic waste intocompost. Through discussion and social intervention, this research has encouraged communityabout the benefits of organic waste as a raw material for making compost.